Deferred Radiotherapy After Debulking of Non-functioning Pituitary Macroadenomas: Clinical Outcomes - Nicholas, Sarah E.; Salvatori, Roberto; Quinones-Hinojosa, Alfredo; Redmond, Kristin; Gallia, Gary; Lim, Michael; Rigamonti, Daniele; Brem, Henry; Kleinberg, Lawrence (Frontiers in Oncology, 2019)
Background: To describe the outcome for a cohort of patients with non-functioning pituitary macroadenomas (NFPMA), managed by debulking surgery with radiation therapy delayed until progression. Methods: 267 patients were treated surgically for pituitary tumors at our institution between 1997 and 2005. 126 patients met the inclusion criteria of NFPMA. They were followed for at least 2 years. Results: At presentation, 58% of patients had objectively decreased visual function, 66% had endocrine abnormalities, and 46% had headaches. Of the entire cohort, 75% of tumors abutted the optic chiasm and 87% had suprasellar extension. Over a median follow up of 112 months from surgery, 52% of patients had evidence of radiographic tumor progression, and 39% required additional treatment. There was a significant difference freedom from progression and in the number of patients receiving additional treatment with preoperative adenoma size of <2cm vs >2cm (p<0.05). Conclusion: Close observation with radiation therapy delayed until the time of progression is an appropriate option for patients presenting with initial adenoma size <2cm, and can be considered for those with initial sizes up to 4cm, as the majority of patients do not require further intervention for ten or more years, thereby meaningfully postponing the risks of radiotherapy.